Carnian–Norian (Late Triassic) climate change: Evidence from conodont oxygen isotope thermometry with implications for reef development and Wrangellian tectonics - Sun, Yadong; Orchard, M. J.; Kocsis, T.; Joachimski, Michael (Earth and Planetary Science Letters, 2020)
The Carnian–Norian (C–N) transition (Late Triassic) has long been postulated as an interval of major climatic changes, though the nature of such changes and their ecological impact remains largely unexplored. We use oxygen isotopes measured on monogeneric conodont assemblages (δ18OPO4) from the Canadian Cordillera to trace seawater temperature evolution at the western margin of Pangea and in the allochthonous Wrangellia Terrane. Different conodont taxa show conspicuous offsets in δ18OPO4, suggesting that they had preferential habitat depths and genus-specific temperature corrections must be applied. Thus, δ18OPO4 from the Williston Lake sections indicates low mid-latitude sea surface temperatures (SSTs) ranging from ∼28 to 35 °C, favouring a generally warm Late Triassic climate scenario. The parvus Subzone of C–N transition, which marks the peak faunal turnover, records major climatic perturbations: SSTs peaking at ∼34 °C then decreasing to ∼29 °C. This is followed by a quick temperature rebound and a second pulse of cooling from 33 to 27 °C in the asymmetrica-Norigondolella Subzone, marking the coldest temperatures in the ∼20 Myr study interval. A secular warming trend towards the late Norian reinstated after the transient cooling in the earliest Norian, coinciding with reef expansions in the Late Triassic. The middle–late Norian (Alaunian 3–Sevatian 1) represents a hothouse climate comparable to the Paleocene–Eocene Thermal Maximum and its warmth supressed both diversity and origination rates of reef-building biota. Early Norian δ18OPO4 data from Frederick Island, Haida Gwaii (part of the Wrangellia Terrane) are more depleted in 18O compared to coeval samples from the Black Bear Ridge, indicating ∼3–5 °C warmer temperatures than the Laurentian epicontinental sea. The temperature difference supports a more southern, probably sub-equatorial position for at least part of the Wrangellia Terrane during the earliest Norian.
CRIS-Team Scopus Importer:2020-01-31
Keywords: faunal turnovers; Late Triassic; palaeoceanography; palaeothemometry; reef development; Wrangellia Terrane